If you mean x^4 + 3x^2 +2, then you would use any letter.
Say y = x^2
therefore x^4 + 3x^2 +2 must = y^2 + 3y + 2
you can now factorise this:
(y+2)(y+1)
so y = -2 or y = -1
Remember, y = x^2
so, -2 = x^2. square root this. But if you remember what you've been taught, then you cannot square root a (-). So, there are no solutions. This means that the line on the graph will not intersect the x-axis.
I hope this is what you are looking for.
(x2 + 1)(x - 3)
3x2 + 30x + 48 is a quadratic polynomial. If 3x2 + 30x + 48 = 0, then: 3(x + 2)(x + 8) = 0 ⇒ x + 2 = 0 → x = -2 or x + 8 = 0 → x = -8
The degree of this polynomial is 2.
3x2 - 2x + 3
Set the equation equal to zero. 3x2 - x = -1 3x2 - x + 1 = 0 The equation is quadratic, but can not be factored. Use the quadratic equation.
x3 - 3x2 + x - 3 = (x2 +1)( x - 3)
3x2 - 5x - 2 can be factored into (3x + 1) (x - 2)
(x2 + 1)(x - 3)
3x2-7x-20 = (3x+5)(x-4) when factored
3x2 + 30x + 48 is a quadratic polynomial. If 3x2 + 30x + 48 = 0, then: 3(x + 2)(x + 8) = 0 ⇒ x + 2 = 0 → x = -2 or x + 8 = 0 → x = -8
21x3-35x2+14x = 7x(3x2-5x+2)
x(x + 2)(x - 5)
Answer this ques Which polynomial represents the sum below?(-x3 + 3x2 + 3) + (3x2 + x + 4)tion…
The degree of this polynomial is 2.
3x2-9x-30 =3x2+6x-15x-30 =3x(x+2)-15(x+2) =(3x-15)(x+2) OR 3(x - 5)(x+2)
3x2 - 2x + 3
3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x+2) - 4(x+2) = (3x-4)*(x+2)